An Evaluation of English Materials Based on the Needs of Health Promotion Department Students at Health Polytechnic of Padang - Sari, Revi Nilam; Fatimah, Sitti (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
. English class in Health Promotion Department faced many obstacles. Those might be related to low English proficiency students, inappropriate learning materials and the ignorance of need analysis. To overcome the obstacles, need analysis is regarded as the most crucial stage. It covered a wide range of activities coping with either the students’ learning needs or their target needs and would begin by analyzing the needs of curriculum demand. It is known as needs analysis. Needs analysis is assumed as the starting point to choose the suitable subject material to fulfill the demand of work field. Therefore, an evaluation of teaching materials based on the needs of Health Promotion Department Students at Health Polytechnic of Padang is required to conduct as the purpose of this research.This research was designed as a survey research. It involved 107 respondents who registered as all active students of Health Promotion Department from the first until the third year; enroll 2017 – 2019 academic years. The data were collected through questionnaire and observation document. The data was analyzed by using quantitative and qualitative method. The questionnaire was analyzed by using quantitative method, meanwhile document observation from the syllabus and questionnaire from the students were analyzed by using qualitative. The findings of this research concluded that the teaching materials on the syllabus of Health Promotion Department Padang have been enough appropriate with the students’ need in short-term (during study process); and long-term (for working life); it was proven by, or a half of them have been appropriate. However, the implementation of the four skills of English has been not appropriate applied yet, since the teaching materials gave for reading more. Teaching English with specific topic that related to the students’ major for all language skills would make them become more enthusiastic. This would be a recommendation to the institution, curriculum designer and course designer to consider the result of this research. The new syllabus and module should be recommended.